Ministry Of Finance Decree No. 117 For The Year 2015 Amending Certain Provisions of the Executive Regulations Of the Income Tax Law, As Issued By Minister of Finance's Decree No. 991 Of The Year 2005 = وزارة المالية قرار رقم 117 لسنة 2015 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على الدخل الصادرة بقرار وزير المالية رقم 991 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic